2020
DOI: 10.1111/nph.16845
|View full text |Cite
|
Sign up to set email alerts
|

Combined high leaf hydraulic safety and efficiency provides drought tolerance in Caragana species adapted to low mean annual precipitation

Abstract: Clarifying the coordination of leaf hydraulic traits with gas exchange across closely-related species adapted to varying rainfall can provide insights into plant habitat distribution and drought adaptation. The leaf hydraulic conductance (K leaf), stomatal conductance (g s), net assimilation (A), vein embolism and abscisic acid (ABA) concentration during dehydration were quantified, as well as pressure-volume curve traits and vein anatomy in 10 Caragana species adapted to a range of mean annual precipitation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
88
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 81 publications
(156 reference statements)
9
88
1
Order By: Relevance
“…Interestingly, our result also showed that arid species had higher K leaf at a given P50 leaf than humid species. This result partially supported a recent study about interspecific variations in leaf hydraulic traits of 10 Caragana species from a range of rainfall environments, which indicates that high K leaf plays a role for species adapted to low rainfall habitats because high leaf hydraulic efficiency may match the requirement of high transpiration caused by high vapour pressure deficit and protect leaves from overheating during drought conditions [41]. Therefore, shifts of the hydraulic safety-efficiency trade-off across different water environments may provide a way to elucidate plants' hydraulic adaptation to drought.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, our result also showed that arid species had higher K leaf at a given P50 leaf than humid species. This result partially supported a recent study about interspecific variations in leaf hydraulic traits of 10 Caragana species from a range of rainfall environments, which indicates that high K leaf plays a role for species adapted to low rainfall habitats because high leaf hydraulic efficiency may match the requirement of high transpiration caused by high vapour pressure deficit and protect leaves from overheating during drought conditions [41]. Therefore, shifts of the hydraulic safety-efficiency trade-off across different water environments may provide a way to elucidate plants' hydraulic adaptation to drought.…”
Section: Discussionsupporting
confidence: 87%
“…Here, our results showed that 71 and 80% loss of leaf hydraulic conductance (PLC) occurred at −3.2 MPa in two isohydric species and 40% and 44% PLC at −3.2 MPa and 88% and 82% PLC at −6.0 MPa in the two anisohydric species, respectively, suggesting that leaf xylem conduit embolism occurred during dehydration in all species. Indeed, the results from the optical method also showed that discrete embolisms propagate in the midrib at ψ leaf reaching approximately −4.0 MPa in six Caragana species, including two C. intermedia and C. microphylla studied here (Yao et al, 2020). Therefore, we proposed that hydraulic impairment may be a potential candidate for explaining the slow recovery of g s after the release of drought (Creek et al, 2018; Skelton et al, 2017).…”
Section: Discussionmentioning
confidence: 52%
“…K leaf P 50 is considered to be important in influencing species distribution in environments across water availability gradients at local and global scales (Blackman, Brodribb, & Jordan, 2012; Blackman et al, 2014; Nardini & Luglio, 2014; Yao et al, 2020). Our findings in this study revealed that two Caragana species with anisohydric traits have a stronger ability to resist hydraulic loss (more negative K leaf P 50 ) than two Caragana species with isohydric traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants invest high amounts of energy to build a safe and effective water transport system (mainly comprised of the vascular bundles) (Brodribb et al, 2017;Waseem et al, 2021). Furthermore, plants have evolved a fully functional signalling network for the optimal adjustment of stomatal aperture, aiming to regulate water-use efficiency (WUE) (Xiao et al, 2018), such that it may be maximal under a wide range of environmental conditions (Cowan & Farquhar, 1977;Brodribb et al, 2009;McAdam & Brodribb, 2012;Yao et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%